2015
DOI: 10.1063/1.4917031
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase measurements of mono-fluoro-benzoic acids and the dimer of 3-fluoro-benzoic acid

Abstract: The microwave spectrum of the mono-fluoro-benzoic acids, 2-fluoro-, 3-fluoro-, and 4-fluoro-benzoic acid have been measured in the frequency range of 4-14 GHz using a pulsed beam Fourier transform microwave spectrometer. Measured rotational transition lines were assigned and fit using a rigid rotor Hamiltonian. Assignments were made for 3 conformers of 2-fluorobenzoic acid, 2 conformers of 3-fluorobenzoic acid, and 1 conformer of 4-fluorobenzoic acid. Additionally, the gas phase homodimer of 3-fluorobenzoic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The doubly hydrogen bonded carboxylic acid dimers that exhibited the tunneling motion had C2v(M) symmetry and a symmetric double-well potential for the tunneling motion. Proton tunneling between identical molecules has also been observed for the homodimers of 3-fluoro-benzoic acid 5 and acrylic acid. 6 Calculations have been reported for the problem of tunneling in the asymmetric double-well potentials.…”
Section: Introductionmentioning
confidence: 86%
“…The doubly hydrogen bonded carboxylic acid dimers that exhibited the tunneling motion had C2v(M) symmetry and a symmetric double-well potential for the tunneling motion. Proton tunneling between identical molecules has also been observed for the homodimers of 3-fluoro-benzoic acid 5 and acrylic acid. 6 Calculations have been reported for the problem of tunneling in the asymmetric double-well potentials.…”
Section: Introductionmentioning
confidence: 86%
“…The intramolecularly hydrogen bonded trans-II conformer of 2FBA is also a well-defined minimum with a high energy barrier (40.4 kJ•mol −1 ) of conversion into cis-II (see Figure 4, bottom-left panel), and has an expected population in the gas phase at room temperature of ca. 2% [16], justifying its experimental observation in the microwave experiment [18]. Trans-II was not detected in the deposited cryogenic matrices [16] most probably because its expected population in the matrix is below the sensitivity of the technique (the infrared spectra is complex, showing the vibrational signatures of the two cis conformers and the spectra of trans-II conformer is not much different from those of the cis forms, which complicates its experimental detection by this technique).…”
Section: Conformers and Barriers To Internal Rotationmentioning
confidence: 96%
“…On the other hand, the trans conformer of BA has never been observed experimentally. In the case of 2FBA, the intramolecularly hydrogen bonded conformer of 2FBA (trans-II) was detected in gas phase (together with the two cis conformers) by microwave spectroscopy [18], and it has been produced in argon and N 2 cryomatrices as result of vibrational excitation of the cis conformers (using infrared narrowband in situ irradiation) [16]. The existence of the highest energy trans-I conformer of 2FBA was inferred indirectly in the matrix isolation conformational studies reported in Ref.…”
Section: Conformers and Barriers To Internal Rotationmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured lines and deviations of lines calculated with the "best fit" parameters are listed in Tables S1, S2, and S3 in the supplementary material. 26 The molecular parameters are given in Table II. The three conformers have been identified as the hydrogen bonded (O-H· · · F) species (2-F conformer 1) and the two hydrogen bonded (O-H· · · O) conformers (2-F conformers 2 and 3) have been predicted to be planar, with the angles α of 0…”
Section: A 2-fluoro-benzoic Acid (I)mentioning
confidence: 99%